Biomass derived Fibers as a Substitute to Synthetic Fibers in Polymer Composites. Issue 6 (24th November 2020) - Qasim, Umair; Ali, Muzaffar; Ali, Touqeer; Iqbal, Rameez; Jamil, Farrukh
Abstract: Advancement in science and technology provides the significant opportunities to utilize the plant fibers (unnoticed materials), which are cheap, abundant, sustainable, and biodegradable. A combination of polymer with the untreated and treated fibers, extracted from lignocellulosic biomass, has been getting significant attention because of their low cost, ecofriendly nature, and enhanced mechanical performance. This article delivers an explicit overview of the plant fibers, extraction and pretreatment of the plant fibers, development of the plant fibers reinforced polymeric composites, and the mechanical properties associated with these biocomposites. A special focus is concentrated on the pretreatment of hydrophilic plant fibers for better compatibility with the polymers, to obtain the enhanced composites having desirable properties. Finally, the effects of several pretreatments on the tensile and water absorption properties of the plant fibers reinforced composites has been included in detail for the better understanding of their practical applications. Abstract : The use of petroleum‐based synthetic materials has caused depletion of the fossil resources and associated environmental problems. Here several treatments and processing techniques are discussed that have been used on plant fibers to enhance their interfacial adhesion with the polymer matrix in order to develop sustainable plant fiber reinforced polymer composites.